Racionalita komunikačnej odozvy podniku ako základ posilňovania community managementu v online prostredí - Adam Madleňák (Ekonomika a Spoločnosť)
The growing influence of freedom of expression is increasingly evident in the expanding online space, where individuals share various opinions, often without regard for their truthfulness or credibility. This trend is particularly noticeable in the marketing communications of businesses, which, in their efforts to enhance their reputation or maintain a consumer-friendly image, must actively respond to these online comments. To effectively manage their reputation, businesses not only need to track and identify mentions of their company and products in the digital world but also prepare appropriate communication responses. These responses are key to building and nurturing customer relationships, forming an essential part of a strategic community management approach. The article, drawing from empirical survey results, emphasizes a key conclusion: businesses generally prefer to offer brief, factual responses rather than in-depth explanations when addressing public feedback. This approach aims to curb the spread of misinformation, ensuring that responses remain clear and direct while minimizing the risk of distortion, incompleteness, or falsehoods in the information shared with the public.